How modern is Philippine agriculture and fisheries? the Agriculture and Fisheries Modernization Act after a quarter century - Briones, Roehlano M. (Quezon City, Philippines Philippine Institute for Development Studies, 2023)
"The Agriculture and Fisheries Modernization Act (AFMA) envisions a sustainable and equitable development of the agriculture and fisheries sector. A quarter century since its passage, to what extent has the Philippine agriculture and fisheries sector been modernized? This volume assessed the implementation of AFMA programs and the sector's performance in relation to the attainment of AFMA's objectives. The analyses revealed implementation gaps and provided recommendations to address them."--Back cover.
Chapter 1 Modernizing Agriculture and Fisheries: Overview of Issues, Trends, and Policies / Roehlano M. Briones --Chapter 2 Market and State in Philippine Agricultural Policy / Roehlano M. Briones -– Chapter 3 Agricultural Technology and Innovations: Why Does the Agricultural Production Level Remain Low Despite Increased Investments in Research and Extension? / Rowena D. Baconguis -– Chapter 4 How Much Has People Empowerment Progressed among Small Farmers and Fisherfolk?: State of People’s Organizations in the Philippines / Danilo A. Songco –- Chapter 5 To What Extent Has Philippine Agriculture Undergone Integration and Consolidation?: The State of Agri-enterprise in the Philippines / Arlene B. Inocencio, Alexis B. Baulita, and Albert Dale B. Inocencio -– Chapter 6 Are Agriculture and Fisheries Ascending the Value-Added Ladder? The State of Agricultural Value Chains in the Philippines / Karlo Fermin S. Adriano and Lourdes S. Adriano -– Chapter 7 Philippine Structural Transformation and Industry Dispersal in the Context of Technological Change / Leonardo A. Lanzona Jr. –- Chapter 8 Enhancing Profits and Incomes in Agriculture and Fisheries / Roehlano M. Briones –- Chapter 9 Is Food Supply Accessible, Affordable, and Stable?: The State of Food Security in the Philippines / Ivory Myka R. Galang –- Chapter 10 How Well Has Environmental Protection Been Ensured for the Fisherfolk and Farmers?: Sustainable Development of Philippine Fisheries and Agriculture / Maria Corazon M. Ebarvia –- Chapter 11 How Modern Is Philippine Agriculture and Fisheries?: Synthesis / Roehlano M. Briones.
Includes bibliographical references.
Keywords: Agriculture -- Philippines -- Economic aspects; Agricultural development projects -- Philippines -- Evaluation; Agricultural laws and legislation -- Philippines; Fishery law and legislation -- Philippines; Agriculture and state -- Philippines; Fisheries -- Philippines